Constant Power Control of Diesels in DMU Based on PI Control - ZHOU Yang; DONG Yukang (Kongzhi Yu Xinxi Jishu)
When a diesel engine operates at non constant power output, it not only has low fuel efficiency but may also generate significant mechanical stress, leading to wear and damage of mechanical components. In order to ensure the efficient operation of diesels within diesel multiple units (DMU), this paper proposes a proportional-integral (PI) control approach based on the operational mode of the diesel generator sets featuring constant power output. This method was devised to steadily synchronize power of the traction systems on the load side with the target output power of the diesel generator sets. In turn, constant power operation on the load side guarantees a constant power output from the generator sets, thereby improving the fuel economy of the diesels. Through simulation and experimental tests, steady state fluctuations in load power were maintained within ±2%, demonstrating the effective constant power operation and the real-time alignment of load power with the target value.